2017
DOI: 10.1021/acsami.6b16509
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Release of Brimonidine from a New Composite Drug Delivery System for Treatment of Glaucoma

Abstract: A novel layered double hydroxide (LDH) nanoparticle/thermogel composite drug delivery system (DDS) for sustained release of brimonidine (Bri) has been designed, prepared, and characterized in this study for treatment of severe glaucoma. Brimonidine is first loaded onto LDH (Bri@LDH) nanoparticles, which are then dispersed in the thermogel consisting of plenty of micelles based on poly(dl-lactic acid-co-coglycolic acid)-polyethylene glycol-poly(dl-lactic acid-co-coglycolic acid) (PLGA-PEG-PLGA) copolymer. The B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 49 publications
0
72
0
Order By: Relevance
“…Laponite in the gel is able to absorb host‐derived bioactive molecules and retain them for the formation of native ECM after degradation of PLGA‐PEG‐PLGA hydrogel. For specific application in the eye, an injectable therapeutic matrices based on triblock (PLGA‐PEG‐PLGA) was successfully tested in in vivo study for glaucoma treatment . In this study, the thermogel showed sustained‐delivery of at least 7 days, and could effectively modulate the relief of intra‐ocular pressure.…”
Section: Types Of Noncovalent Polymeric Hydrogelsmentioning
confidence: 99%
“…Laponite in the gel is able to absorb host‐derived bioactive molecules and retain them for the formation of native ECM after degradation of PLGA‐PEG‐PLGA hydrogel. For specific application in the eye, an injectable therapeutic matrices based on triblock (PLGA‐PEG‐PLGA) was successfully tested in in vivo study for glaucoma treatment . In this study, the thermogel showed sustained‐delivery of at least 7 days, and could effectively modulate the relief of intra‐ocular pressure.…”
Section: Types Of Noncovalent Polymeric Hydrogelsmentioning
confidence: 99%
“…Layered double hydroxides (LDH) can be efficient ocular delivery vehicles for a series of active compounds, such as diclofenac sodium, phacolysin and brimonidine. [15][16][17] Based on the evidence that PepT-1 has been identified in the corneal epithelium of humans, we have recently reported an organic-inorganic intercalated nanocomposite of PRN loaded CTS-glutathione-valine-valine layered double hydroxides (CG-VV-PRN-LDH) for topical ocular drug delivery. 18 The multifunctional nanocomposites with target ligand of dipeptide VV have been demonstrated with active targeting of PepT-1 in animals and at the cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…35 Efforts have been devoted to develop drug delivery systems to extend drug activity, thus reducing dosing frequency and improving patient compliance. 68 Topical drug vehicles are expected to be biocompatible, mucoadhesive, and have suitable viscosity. 9, 10 Lipids, Hyaluronic acid, PEG, PLGA and chitosan are commonly used polymers as topical drug delivery carriers and have been fabricated into particles and hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…36, 37 The application of hydrogels can result in prolonged pre-corneal residence time and increased ocular bioavailability. 8, 38, 39 Our group has developed a hybrid dendrimer hydrogel/PLGA nanoparticles platform and used it to fabricate a brimonidine/timolol maleate combination formulation for topical application. 38 This platform is capable of enhancing drug bioavailability and substantially sustaining drug activity following topical administration.…”
Section: Introductionmentioning
confidence: 99%